2014
DOI: 10.1111/iej.12256
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology, incidence and morphology of the C‐shaped root canal system and its impact on clinical endodontics

Abstract: The C-shaped root canal constitutes an unusual root morphology that can be found primarily in mandibular second permanent molars. Due to the complexity of their structure, C-shaped root canal systems may complicate endodontic interventions. A thorough understanding of root canal morphology is therefore imperative for proper diagnosis and successful treatment. This review aims to summarize current knowledge regarding C-shaped roots and root canals, from basic morphology to advanced endodontic procedures. To thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 140 publications
(284 reference statements)
2
89
0
21
Order By: Relevance
“…Plenty of document information studied its incidence, morphology and clinical impact [11,12]. It is reported that the prevalence of C-shaped root canals in mandibular second molars was 39% in the Chinese population [13].…”
Section: Discussionmentioning
confidence: 99%
“…Plenty of document information studied its incidence, morphology and clinical impact [11,12]. It is reported that the prevalence of C-shaped root canals in mandibular second molars was 39% in the Chinese population [13].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these commercial systems, Kato and colleagues [98] recently reported that freely accessible 3D models of teeth embedded into portable document format (PDF) files would constitute a valuable tool for dental students as well. In their study, four publication-embedded tooth models based on µCT datasets were presented that interactively permit the comparison of a tooth with regular root canal morphology and three teeth showing different types of C-shaped root canals [98 p. 1024].…”
Section: Interactive Three-dimensional Models Of Human Teethmentioning
confidence: 99%
“…The root canal system has been classified based on the canal pattern, and includes lateral branches, additional branches, and/or fused canals; the most popular criteria for the classification of root canals is the Vertucci's criteria [125,126]. A C-shaped root in the mandibular second molar is frequently found in the Japanese [130,131,[136][137][138][139][140] (reviewed by Kato et al [141]), and this unique root structure exhibits a complex root canal system.…”
Section: Morphological Study Of the Pulp Cavitymentioning
confidence: 99%